Anatomical and Visual Outcome of Rhegmatogenous Retinal Detachment Managed with Scleral Buckling at a Tertiary Eye Centre in Nepal - Rijal, Roshija Khanal; Byanju, Raghunandan; Pandey, Araniko; Mourya, Deepesh (Nepalese Journal of Ophthalmology, 2018)
Objective: To study the anatomical status and visual outcome of scleral buckling surgery in rhegmatogenous retinal detachment (RRD) at tertiary eye care center in Nepal. Method: This is a prospective, noncomparative, consecutive, interventional study of rhegmatogenous retinal detachment managed with scleral buckling surgery performed in Lumbini Eye Institute, Nepal. All the patients underwent surgery by a single experienced surgeon and had at least 3 months follow up. Result: A total of 50 patients (50 eyes) were operated, 38 males and 12 females, with a mean age of 39.46. Retinal reattachment was achieved in 46 (92%). Improved best corrected visual acuity (BCVA) was seen in 84%, whereas in 8% BCVA was same and deteriorated in another 8%. Conclusion: Rhegmatogenous retinal detachment is one of the common causes of visual impairment and blindness. Timely surgical management with scleral buckling surgery can give good anatomical and visual outcome.